Modulation of Lipid and Glucose Profiles in Hyperglycemic and Hypercholesterolemic Animals by Nanocapsules of Purple Yam Anthocyanin Extract - Tamaroh, Siti; Candraruna, Dipta Bthari; Sari, Yuli Perwita; Kanetro, Bayu (Department of Technology of Agricultural product (THP) Jambi University, 2026)
Purple yam, rich in anthocyanins, has potential benefits for dyslipidemia and diabetes. Encapsulation into nanocapsules improves its stability and bioavailability. This study aimed to evaluate the effects of purple yam anthocyanin extract (PYAE) nanocapsules on high-fat diet and streptozotocin (STZ)-induced diabetic rats. Diabetic rats induced with high-fat diet and streptozotocin (STZ) were divided into control and treatment groups receiving simvastatin, metformin, or purple yam anthocyanin extract (PYAE) nanocapsules (80-240 mg/200 g bq) for four weeks. Various parameters were observed, including body weight, blood glucose, serum insulin, lipid profile, and histopathology of the liver and pancreas. The results indicated that treatment with purple yam anthocyanin extract nanocapsules improved body weight, blood glucose levels, insulin levels, and lipid profiles compared to the diabetic rat group. Specifically, the blood glucose level in the group receiving 240 mg/200 g bw decreased significantly from 264.26 mg/dL to 91.70 mg/dL (p<0.05). In addition, body weight and insulin level increased, with insulin rising by 529.89 pg/mL from an initial level of 469.71 pg/mL. Furthermore, PYAE nanocapsules improved the lipid profiles of dyslipidemic rats by reducing triglycerides, cholesterol, and LDL levels while increasing HDL levels (p<0.05). Histopathological examination revealed that PYAE nanocapsule alleviated damage to pancreatic and liver tissues in diabetic rats.